Xylanase production by Bacillus circulans D1 using maltose as carbon source - Bocchini, D. A. [UNESP]; Gomes, E. [UNESP]; Da Silva, R. [UNESP] (Humana Press Inc, 2008)
Bacillus circulans D1 is a good producer of extracellular thermostable xylanase. Xylanase production in different carbon sources was evaluated and the enzyme synthesis was induced by various carbon sources. It was found that D-maltose is the best inducer of the enzyme synthesis ( 7.05 U/ mg dry biomass at 48 h), while D-glucose and D-arabinose lead to the production of basal levels of xylanase. The crude enzyme solution is free of cellulases, even when the microorganism was cultivated in a medium with D-cellobiose. When oat spelt xylan was supplemented with D-glucose, the repressive effect of this sugar on xylanase production was observed at 24 h, only when used at 5.0 g/ L, leading to a reduction of 60% on the enzyme production. on the other hand, when the xylan medium was supplemented with D- xylose ( 3.0 or 5.0 g/ L), this effect was more evident ( 80 and 90% of reduction on the enzyme production, respectively). Unlike that observed in the xylan medium, glucose repressed xylanase production in the maltose medium, leading to a reduction of 55% on the enzyme production at 24 h of cultivation. Xylose, at 1.0 g/ L, induced xylanase production on the maltose medium. on this medium, the repressive effect of xylose, at 3.0 or 5.0 g/ L, was less expressive when compared to its effect on the xylan medium.
Keywords: Xylanase; maltose; induction; repression; Bacillus circulans